THE ROLE OF SOCIAL RECOGNITION AND ACHIEVEMENT SIGNALING IN CONSUMER DECISION-MAKING - Sutan Mahendra Adika Wijaya; Burhanudin Burhanudin (SEAN Institute, 2023)
The psychological needs of social recognition and achievement signaling may motivate the purchase intention of luxury products. Luxury products are identical in number and for a limited community. Hence, the emergence of masstige brands that carry luxury for the masses is crucial to investigate. This study aims to investigate the effect of social recognition and achievement signaling on willingness to purchase a masstige brand and further, how it impacts attitudinal loyalty. A total of 240 smartphone users in Indonesia participated in this study. The data were analyzed using SEM (Structural Equation Modeling). This study found achievement signaling motivates willingness to purchase a masstige brand and further, drives attitudinal loyalty to the brand. This study did not find support that social recognition drives willingness to purchase a masstige brand.